Social Media and Perceived Political Polarization: Role of Perceived Platform Affordances, Participation in Uncivil Political Discussion, and Perceived Others’ Engagement - Macau K. F. Mak; Mengyu Li; Hernando Rojas (Social Media + Society, 2024)
This research applies a perceived affordance approach to examine the distinctive role of social media technologies in shaping (mis)perceptions of political polarization. We argue that users’ perceptions of platform affordances influence both (a) their self-participation in uncivil political discussion on social media and (b) perceptions of others’ engagement, which eventually shape their perceptions of polarization. Our analysis of US survey data found that perceptions of lower privacy and stronger network association on Facebook are related to perceptions of a higher level of uncivil discussion by other users, which in turn predicts greater perceived polarization. Perceptions of higher anonymity relate to higher self-participation in uncivil discussion, which is surprisingly associated with perceptions of reduced polarization. Our follow-up experimental study illustrated that participants with more frequent engagement in uncivil discussion, irrespective of interacting with civil or uncivil comments, showed consistently higher levels of intrapersonal reflection, which reduces perceived polarization.